A comparison between two indices derived from automated pupillometry devices - Carlotta Bandoni; Khalil Mounir; Francesca Iannuzzi; Andrea Berardino; Fabio Tarantino; Mohammed Rabi Andaloussi; Fabio Silvio Taccone; Denise Battaglini; Nicolo ’ Antonino Patroniti; Chiara Robba (Journal of Clinical Monitoring and Computing, 2026)
Abstract Automated pupillometry provides a standardised, quantitative, highly reproducible measurement of the pupillary light reactivity and other pupillary variables. The Neurologic pupillary index (NPi) has shown good prognostic value in patients with acute brain injury and cardiac arrest. However, few data on the comparison of NPi with a recently introduced index (quantitative pupillary index, QPI) are available. To compare the performance of two commercially available automated pupillometry devices, and in particular QPI and NPi, in a cohort of neuro-critically ill patients. Single-center observational study, including adult (> 18 years) patients admitted to a neuro-intensive care unit over a 6-month period. Pupillary reactivity was assessed in both eyes of each patient using the two pupillometers currently available, the Neuroptics NPi-300 (Neuroptics, Irvine, CA, USA) and the NeuroLight (ID-Med, Marseilles, France). A total of 73 patients were included in the final analysis, with a median age of 65 years (interquartile range [IQR] 54–77). The mean bias between the two pupillometers was 0.44 mm (95% Limit of Agreement [LoA] − 0.43 mm to 1.31 mm) for pupil diameter, 0.57% (95% LoA − 7.63% to 8.77%) for pupillary reactivity, and − 0.82 (95% LoA − 2.70 to 1.05) for NPi vs. QPI comparison. A very strong correlation was found between the two devices in terms of pupil diameter measurement (ρ = 0.91; 95% Confidence Interval [CI] 0.86 to 0.95; p < 0.0001) and pupil reactivity (ρ = 0.92; 95% CI 0.87 to 0.95; p < 0.0001). NPi and QPI were well correlated (ρ = 0.75; 95% CI, 0.62–0.84; p < 0.0001). In this cohort study, a significant statistical correlation between the measurements provided by two available pupilometers was found; however, NPi and QPI might not be clinically interchangeable.